DO PRIMARY SCHOOL STUDENTS NEED ORAL LITERATURE? - Lina Novita; Leora Grahadila (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
Oral literature currently seems lost and unknown to students. This article is a description of oral literature. The purpose of this presentation is to make students familiar with oral literature in their area, especially at the Sundanese level. The importance of the introduction of oral literature because oral literature can be used as a reference in behavior. This is because the content of oral literature is full of life lessons and interactions in society. Therefore, it is necessary for schools and local governments to continue to develop and introduce oral literature in schools